Preventive Effect of Albumin Nano TPA Gene Plasmid Ultrasound Microbubble Carrier System on Thrombosis after Cardiac Valve Replacement - Feng Qi; Linlin Zhao; Guohua Cai; Zhendong Sun; Naishi Wu (Journal of Chemistry)
After cardiac valve replacement, most patients will have different degrees of thrombosis, different parts of the thrombus, and even more frequent occurrence of postoperative thrombosis; therefore, the prevention of postoperative thrombosis is particularly important. The purpose of this study was to investigate the preventive effect of albumin nano tPA gene plasmid ultrasound microbubble carrier system on thrombosis, especially in cardiac valve. The experimental control method was used. Firstly, 11 dogs meeting the experimental requirements were selected. Secondly, the data of albumin nanoparticles and microbubbles were analyzed. The average size of albumin particles was 132.0 nm, the average size of microbubbles was 3.1 ± 1.6 μm, and the zeta potential was 13.70 ± 1.95 MV. The concentration of microbubbles was 4.2 ± 1.3 × 10/ml. Finally, 11 dogs were divided into two groups. The experimental group was treated with albumin nanoparticles ultrasound microbubble, and the others were the control group. It was found that the levels of tPA and D-dimer in the experimental group were significantly increased and maintained at a high level at 1 week after operation, and the prothrombin time was detected and the international normalized ratio was calculated at the same time. No significant changes were found in the experimental group.